The grammar of desire: of restraints and controls - Bhaswati, Snigdha (Social Change and Development)
Human bodies have been the primary sites of control, restricted by norms and traditions in order to keep the brahmanical, patriarchal societal order functioning smoothly. The essay here is an attempt at getting a glimpse of lives of a few women in 19th and 20th century Assam- the protagonists of certain selected works of Assamese literature. The idea is to analyze the tales that these literary masterpieces spin and locate the trajectory of lives of the women therein. Puberty, marriage and widowhood have been used as the three main tropes providing vantage points to view the ways in which the lives of these female protagonists have been directed here and the idea is to get a very broad picture of how female sexuality and sexual desires are kept under strict control lest they dare challenge the prevalent hierarchies of the society.- Reproduced
Keywords: Widowhood, Marriage, Puberty, Women